Regulation of sodium transport across epithelia derived from human mammary gland - Wang, Qian (Kansas State University, 2014)
The first aim of this project is to define the cellular mechanisms that account for the low Na[superscript]+ concentration in human milk. MCF10A cells, which were derived from human mammary epithelium and grown on permeable supports, exhibit amiloride- and benzamil-sensitive short circuit current (I[subscript]sc), suggesting activity of the epithelial Na[superscript]+ channel, ENaC. When cultured in the presence of cholera toxin (Ctx), MCF10A cells exhibit greater amiloride sensitive I[subscript]sc at all time points tested, an effect that is not reduced with Ctx washout for 12 hours or by cytosolic pathways inhibitors. Ctx increases the abundance of both beta and gamma-ENaC in the apical membrane and increases its monoubiquitination but without changing total protein and mRNA levels. Additionally, Ctx increases the levels of both the phosphorylated and the nonphosphorylated forms of Nedd4-2, a ubiquitin-protein ligase that regulates ENaC degradation. The results reveal a novel mechanism in human mammary gland epithelia by which Ctx regulates ENaC-mediated Na[superscript]+ transport. The second project aim is to develop a protocol to isolate mammary gland epithelia for subsequent in vitro culture. Caprine (1[superscript]0CME) and bovine mammary epithelia (1[superscript]0BME) were isolated and cultured on permeable supports to study hormone- and neurotransmitter-sensitive ion transport. Both 1[superscript]0CME and 1[superscript]0BME cells were passed for multiple subcultures and all passages formed electrically tight barriers. 1[superscript]0CME were cultured in the presence of hydrocortisone and exhibited high electrical resistance and amiloride-sensitive I[subscript]sc, suggesting the presence of ENaC-mediated Na[superscript]+ transport. 1[superscript]0BME were grown in a complex media in the presence or absence of dexamethasone. In contrast to 1[superscript]0CME, 1[superscript]0BME exhibited no detectable amiloride-sensitive I[subscript]sc in either culture condition. However, 1[superscript]0BME monolayers responded to an adrenergic agonist, norepinephrine, and a cholinergic agonist, carbamylcholine, with rapid increases in I[subscript]sc. Thus, this protocol for isolation and primary cell culture can be used for future studies that focus on mammary epithelial cell regulation and functions. In conclusion, the results from these projects demonstrate that mammary epithelial cells form electrically tight monolayers and can exhibit neurotransmitter- and/or hormone-induced net ion transport. The mechanisms that regulate Na[superscript]+ transport across mammary gland may provide clues to prevent or treat mastitis.
Keywords: Epithelial sodium channel (ENaC); Sodium transport; Mamamry epithelia; Cholera toxin; Short circuit current Isc; Physiology (0719)